2013
DOI: 10.1371/journal.pone.0054633
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression and Phasic Changes in Gene Expression in a Mouse Model of Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common form of arthritis and has multiple risk factors including joint injury. The purpose of this study was to characterize the histologic development of OA in a mouse model where OA is induced by destabilization of the medial meniscus (DMM model) and to identify genes regulated during different stages of the disease, using RNA isolated from the joint “organ” and analyzed using microarrays. Histologic changes seen in OA, including articular cartilage lesions and osteophytes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
118
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 30 publications
25
118
1
Order By: Relevance
“…Further, microarray analyses of genes expressed in knees of mice with surgery-induced OA showed that Ccl2 is upregulated as early as 6 hours and 7 days after surgery when there is no apparent histological changes) relative to sham-operated controls (see online supplementary figure S1A). 18 20 To evaluate whether increased Ccl2 gene expression was sustained through the progression of OA, we analysed synovial Ccl2 expression at 12 weeks after DMM, when significant cartilage degradation is apparent 18 19 21. We found that synovial Ccl2 mRNA was significantly upregulated in DMM-operated compared with sham-operated mice (see online supplementary figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Further, microarray analyses of genes expressed in knees of mice with surgery-induced OA showed that Ccl2 is upregulated as early as 6 hours and 7 days after surgery when there is no apparent histological changes) relative to sham-operated controls (see online supplementary figure S1A). 18 20 To evaluate whether increased Ccl2 gene expression was sustained through the progression of OA, we analysed synovial Ccl2 expression at 12 weeks after DMM, when significant cartilage degradation is apparent 18 19 21. We found that synovial Ccl2 mRNA was significantly upregulated in DMM-operated compared with sham-operated mice (see online supplementary figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, we investigated whether ADAMTS-5 blockade altered mechanical allodynia and associated production of the pro-algesic chemokine, monocyte chemoattractant protein (MCP)-1, by dorsal root ganglia (DRG) neurons [9]. We chose to start treatment 4 weeks after DMM surgery since, by this time, mild structural damage is evident [14-16] and mechanical allodynia has fully developed [8, 9], reflecting an early stage of disease.…”
Section: Introductionmentioning
confidence: 99%
“…We recently generated a microarray dataset that assessed gene expression changes over time during the early stages of OA in a commonly used mouse model 8 . In this model, OA develops after surgical destabilization of the medial meniscus (DMM model).…”
Section: Introductionmentioning
confidence: 99%
“…In order to be able to take a more systems level approach, we examined gene expression changes in the joint as an organ by extracting RNA from a pool of tissues including cartilage, subchondral bone, meniscus and the joint capsule with synovium. Using this dataset, we previously filtered a total of 371 genes into 27 clusters with various temporal gene expression patterns 8 . These clusters included many genes previously associated with OA—such as COMP, MMP14, TIMP2, SDC1, DDR2, TGFB2, MMP13, FMOD, BGN, LECT1, S100B and multiple collagen genes—and elucidated their expression kinetics during the onset of OA.…”
Section: Introductionmentioning
confidence: 99%